English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-04 06:57:18 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

Let the numbers be x and y
product : xy = 6 or y = 6/x
sum : x + y = 6

x + 6/x = 6
x^2 - 6x + 6 = 0
x= [6 ± √(6^2 - 4*1*6) ] / 2
= [6 ± √(36-24)]/2 = (6±√12)/2
= (6 ± 2√3)/2
or
x = 3 +√3 or 3 - √3
if x = 3 + √3 then y = 3 - √3, since x+y=6
(and if x = 3 - √3 then y = 3 + √3, the same two numbers)

so 3 +√3 and 3 - √3 is the answer

checking,
sum: (3 +√3) + (3 - √3) = 6
product: (3 + √3)(3 - √3) = 9 +3√3 - 3√3 - 3 = 6

2006-12-04 07:02:30 · answer #1 · answered by Scott R 6 · 2 0

Let x and y by the numbers. Then

x + y = 6, and
xy = 6

Take the first equation, and note that y = 6 - x, so we substitute this into the second equation.

x(6-x) = 6
6x - x^2 = 6
Bring everything over to the right hand side, to get

x^2 - 6x + 6 = 0

To solve this, we have to either use the quadratic formula, or complete the square. I'm gonna do it the complete the square way (either of them work; one just involves excessive typing).

x^2 - 6x + 9 - 3 = 0
(x-3)^2 - 3 = 0
(x-3)^2 = 3
x - 3 = +/- sqrt(3)
x = 3 +/- sqrt(3)

Therefore, we have two solutions for one number, x.
x = 3 + sqrt(3) or x = 3 - sqrt(3).

Now, we solve for y, using the fact that x + y = 6.
If x = 3 + sqrt(3), then y = 6 - (3 + sqrt(3)) = 3 - sqrt(3)
If x = 3 - sqrt(3), then y = 6 - (3 - sqrt(3)) = 3 + sqrt(3)

Notice that the two answers merge into one because they represent "any two numbers" ("6 and 3" has the same meaning as "3 and 6" should those have been the solution).

x = 3+sqrt(3) , y = 3-sqrt(3) are the two numbers.

2006-12-04 07:08:08 · answer #2 · answered by Puggy 7 · 0 0

let the numbers be a and b

Then a + b = 6 so b = 6 - a
ab = 6

So a(6 - a) = 6
ie 6a - a² = 6
So a² - 6a + 6 = 0
Thus a = (6 ± √(36 - 24))/2
= 6/2 ± ½√(12)
= 3 ± √(3)

So one number is 3 + √(3)
and the other number is 3 - √(3)

So a + b = 3 + √(3) + 3 - √(3) = 6
ab = [3 + √(3)][3 - √(3)] = (3)² - (√(3))² = 9 - 3 = 6

2006-12-04 07:04:47 · answer #3 · answered by Wal C 6 · 1 1

3 & 2

2006-12-04 09:12:41 · answer #4 · answered by Johnathan 2 · 0 2

x+y=6
xy=6
x(6-x)=6
6x-x^2-6=0
x^2-6x+6=0
x=(6+/-√(36-24))/2
x=3+/-(1/2)√12=3+/-√3
the numbers are 3+√3 & 3-√3

2006-12-04 07:22:16 · answer #5 · answered by yupchagee 7 · 1 1

3 + SQRT(3)

3 - SQRT(3)

2006-12-04 07:08:43 · answer #6 · answered by sri 1 · 0 0

fedest.com, questions and answers